Design Application Performance Dashboard Visualization Machine For Harbour Mobile Crane (HMC) At PT. BJTI - Hadi, Muhammad Miftahol; Wurijanto, Tutut; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. Berlian Jasa Terminal Indonesia (PT. BJTI) is a company with main business in the service of loading and unloading at the port of Tanjung Perak. Engineering Planning & Administration Division is a part that handles the level of availability of a tool or machine used for the operations of PT. BJTI. Based on current conditions, managers have difficulty in making decisions related to engine performance HMC, because the data required to know engine performance HMC are many and varied and has a high complexity. From the above problems, it is known that the company needs a dashboard application that is able to provide performance information about HMC machines that can assist managers in making decisions and can monitor engine performance HMC and compare with KPI. It was concluded that this application has been able to display visualization information performance condition HMC machine, so it can help the managers to monitoring and control of engine performance HMC. Applications can display notifications to certain conditions, so as to assist managers in making decisions.